The Effect of Corporate Governance, Regulatory Compliance, and Company Size on Enterprise Risk Management of Kalimantan Regional Development Banks - Darmansyah, Darmansyah; Said, Laila Refiana; Swandari, Fifi (AIBPM Publisher, 2024)
This study analyzes the effect of corporate governance, regulatory compliance, and company size on enterprise risk management. The subject of this study is regional banking companies located in the Kalimantan using data during 2014-2023. The results of the data test show that corporate governance, regulatory compliance, and company size affect the risk management of a company. The findings of this study support the importance of developing good governance and complying with applicable procedures in implementing more effective risk management. In addition, the larger a company, the more of focus on risk management to become more effective organization.